Snow falling on cedars - Guterson, David (New York : Vintage Books, 1995)
In 1954, Ishmael Chambers, a local reporter who lost an arm in the war, covers the murder trial of a Japanese American fisherman, whose wife had been Ishmael's childhood sweetheart.
1080
PEN/Faulkner Award, 1995.
Keywords: Japanese Americans -- Washington (State) -- Fiction; Trials (Murder) -- Washington (State) -- Fiction; Journalists -- Washington (State) -- Fiction; Washington (State) -- Fiction; Legal stories